antwoord

Eerst de afgeleide: 

$
\eqalign{
  & f(x) = 2x\left( {\sqrt x  - x} \right)  \cr
  & f'(x) = 2\left( {\sqrt x  - x} \right) + 2x\left( {{1 \over {2\sqrt x }} - 1} \right)  \cr
  & f'(x) = 2\sqrt x  - 2x + \sqrt x  - 2x  \cr
  & f'(x) = 3\sqrt x  - 4x \cr}
$

Stel $f'(x)=0$ en los op.

$
\eqalign{
  & 3\sqrt x  - 4x = 0  \cr
  & 3\sqrt x  = 4x  \cr
  & 9x = 16x^2   \cr
  & 16x^2  - 9x = 0  \cr
  & x(16x - 9) = 0  \cr
  & x = 0\,\,of\,\,x = {9 \over {16}} \cr}
$

Vul $
x = {9 \over {16}}
$ in de bij f.

$
f({9 \over {16}}) = 2 \cdot {9 \over {16}}\left( {\sqrt {{9 \over {16}}}  - {9 \over {16}}} \right) = {{27} \over {128}}
$

q10307img1.gif

De coördinaten van de top zijn $
\left( {{9 \over {16}},{{27} \over {128}}} \right)
$

©2004-2021 Wiskundeleraar - login